2015
DOI: 10.4048/jbc.2015.18.3.271
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Survival Benefit of Different Chemotherapy Regimens in Patients with T1-2N0 Triple-Negative Breast Cancer

Abstract: PurposeThis study aimed to evaluate the survival benefit of different adjuvant chemotherapy regimens in patients with T1-2N0 triple-negative breast cancer.MethodsOf 67,321 patients who were registered in the Korean Breast Cancer Society nationwide database between January 1999 and December 2008, 4,033 patients with T1-2N0 triple-negative breast cancer were included. The overall survival of patients who did not receive adjuvant chemotherapy was compared with those treated with adjuvant anthracycline and cycloph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Short-interval, frequent follow-up sessions may be helpful for early detection of relapse. Intensified adjuvant treatment for overweight patients, including combination CT ( 23 24 ) and dose-escalated RT ( 25 ), can be attempted as treatment options to improve outcomes. In cases with clinically suspected recurrence, active and immediate diagnostic evaluation and treatment should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Short-interval, frequent follow-up sessions may be helpful for early detection of relapse. Intensified adjuvant treatment for overweight patients, including combination CT ( 23 24 ) and dose-escalated RT ( 25 ), can be attempted as treatment options to improve outcomes. In cases with clinically suspected recurrence, active and immediate diagnostic evaluation and treatment should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with advanced-stage breast cancer received chemotherapy, which was performed in 84.1% (n = 53) of the patients with standard treatment regimens, of which 6 received neoadjuvant chemotherapy before surgical resection. Anthracycline- and taxane-based regimens were commonly used in chemotherapy [ 11 ]. Most patients who underwent BCS received adjuvant RT.…”
Section: Methodsmentioning
confidence: 99%
“…However, other studies have shown that standard adjuvant chemotherapy regimens improve overall survival in TNBC patients, for example, patients with T1/2 node-positive TNBC. 10 Possible limitations to this study should be considered. As this was a retrospective study, follow-up times varied widely.…”
Section: Discussionmentioning
confidence: 98%
“…9 Therapeutic options for TNBC are limited to non-targeted therapies due to a lack of an identified molecular target. 10 Breast conservation surgery is an option for early breast cancer followed by adjuvant radiation therapy; recent reviews suggest that, after adjusting for age at diagnosis, stage, histology and grade, survival was equal or better after breast conservation surgery than mastectomy. 9,11 Conventional radiation treatment involves whole-breast tangential irradiation over 5 weeks, with a subsequent boost to the tumor bed 12 where indicated due to tumor and patient characteristics.…”
Section: Introductionmentioning
confidence: 99%